Intense dose-dense epirubicin, paclitaxel, cyclophosphamide versus weekly paclitaxel, liposomal doxorubicin (plus carboplatin in triple-negative breast cancer) for neoadjuvant treatment of high-risk early breast cancer (GeparOcto—GBG 84): A randomised phase III trial. (January 2019) - Schneeweiss, Andreas; Möbus, Volker; Tesch, Hans; Hanusch, Claus; Denkert, Carsten; Lübbe, Kristina; Huober, Jens; Klare, Peter; Kümmel, Sherko; Untch, Michael; Kast, Karin; Jackisch, Christian; et al.
Abstract: Background: GeparOcto compared efficacy and safety of two chemotherapy regimens in high-risk early breast cancer (BC): sequential treatment with intense dose-dense epirubicin, paclitaxel, and cyclophosphamide (iddEPC) and weekly treatment with paclitaxel plus non-pegylated liposomal doxorubicin (M, Myocet®) with additional carboplatin (PM(Cb)) in triple-negative BC (TNBC). Patients and methods: Patients with cT1c-cT4a-d and centrally assessed human epidermal growth factor receptor (HER)2-positive BC or TNBC were eligible, irrespective of nodal status, luminal B-like tumours only if pN+. Patients were randomised (stratified by BC subtype, Ki67, lymphocyte-predominant BC) to receive 18 weeks of E (150 mg/m 2 ) followed by P (225 mg/m 2 ) followed by C (2000 mg/m 2 ), each q2w for 3 cycles or weekly P (80 mg/m 2 ) plus M (20 mg/m 2 ) plus, in TNBC, Cb (area under curve (AUC) 1.5). HER2-positive BC patients additionally received trastuzumab (6 [loading dose 8]mg/kg q3w) and pertuzumab (420 [840]mg q3w) with all P and C cycles. Primary end-point was pathological complete response (pCR, ypT0/is ypN0), secondary end-points included other pCR definitions, pCR in stratified subpopulations, tolerability and compliance. This trial is registered withClinicalTrials.gov numberNCT02125344 . Results: 945/961 randomised patients started treatment. The median age was 48 years; 7.6% had cT3-4, 46% cN+, 66% G3, 40% HER2-positive, 43% TNBC. pCR rate with iddEPC was 48.3%, with PM(Cb) 48.0%, respectively (PM(Cb) versus iddEPC odds ratio 0.99; 95% confidence interval 0.77–1.28, P = 0.979) with no significant differences observed in TNBC, HER2-positive, luminal B-like subtypes. 16.4% with iddEPC and 34.1% with PM(Cb) discontinued treatment ( P < 0.001), mainly due to adverse events; two patients on PM(Cb) died. Conclusions: In high-risk early BC there is no difference in pCR rates following neoadjuvant treatment with iddEPC or weekly PM(Cb), respectively. iddEPC is one of the effective dose-dense regimens feasible in daily practice. Highlights: In high-risk early breast cancer (BC), pathological complete response (pCR) rates of intense dose-dense epirubicin, paclitaxel, and cyclophosphamide (iddEPC) and weekly paclitaxel plus non-pegylated liposomal doxorubicin with additional carboplatin in triple-negative breast cancer PM(Cb) were similar. Weekly PM(Cb) led to more dose reductions, treatment delays and overall toxicity. In patients with lymphocyte-predominant BC, pCR rate was significantly higher with iddEPC.